Schools making a difference : let's be realistic! school mix, school effectiveness, and the social limits of reform - Thrupp, Martin 1964- (Open University Press, 1999)
Does an effective school really come about through the actions of teachers and school leaders, or does it also require an advantaged student intake? This question reflects a longstanding research debate about whether or not the social class mix of a school's student intake has much effect on individual achievement. Schools Making a Difference: Let's Be Realistic! presents new evidence which suggests that school mix is likely to be important because of the way many school processes are deeply influenced by student intake characteristics. Low socioeconomic schools face numerous intake-related constraints which make them highly resistant to improvement efforts. By suggesting that 'failing' schools are often overwhelmed rather than ineffective, this book provides a sympathetic reappraisal of the performance of teachers and school leaders in such schools. It also offers a critical response to the often unrealistic claims of the school effectiveness and school improvement movement and a fresh critique of market reforms in education.